State, society, and sexuality: an inquiry on the lived experiences of lesbians and gay men in contemporary Singapore - Tan, Mellany Jia Enn (Nanyang Technological University, 2024)
This thesis investigates the lived experiences of lesbians and gay men in contemporary Singapore, a society deeply rooted in heteronormative ideals and heavily influenced by state policies. Qualitative interviews were conducted with 27 lesbian and gay men in Singapore providing insights into how structural conditions shape their everyday lives. Guided by three central inquiries, I explored the impact of state policies on various aspects of their lives from housing and healthcare to identity and societal acceptance. Their narratives revealed how they confront challenges within the workplace, home, and healthcare challenges and how it shapes their experiences within a heteronormative society. The findings illustrate how lived experiences intersect with notions of citizenship within a heteronormative state, unveiling structural inequalities and institutional discrimination. This study explores how state ideals of values of familism and filial piety shape their lives, where participants grapple with the paradox of “singleness” and caregiving responsibilities. The findings uncover the pervasiveness of workplace discrimination how lesbians and gay men navigate that landscape, and the role of gender norms as they navigate through societal perceptions. Finally, this thesis shed light on the intrusive effects of heteronormative expectations, highlighting the impact of the everyday experiences of lesbians and gay men in Singapore.